A Case of Treatment Resistance and Complications in a Patient with Stiff Person Syndrome and Cerebellar Ataxia. (1st October 2019) - Jones, Lliwen A.; Baber, Waqaar; Wardle, Mark; Robertson, Neil P.; Morris, Huw R; Church, Alistair; Llewelyn, John G.; Peall, Kathryn J.
Background: Antibodies against glutamic acid decarboxylase (GAD) are associated with Stiff Person Syndrome (SPS). Case report: A 50-year-old woman presented with symptoms progressed over 9 years, resulting in a cerebellar ataxia and right upper limb tremor. Investigations revealed elevated serum and CSF anti-GAD antibody titres (98.6 and 53.4 μ/ml, respectively). Treatment included intravenous immunoglobulin and immunomodulation (infliximab and rituximab), improving her stiffness, but with no impact on the ataxia-related symptoms. Subsequent high-dose steroids led to diabetic ketoacidosis and unmasking of an insulin-dependent diabetes mellitus. Discussion: This case illustrates several key features: (1) the combined clinical picture of SPS and cerebellar ataxia is a rare phenotype associated with anti-GAD antibodies; (2) the cerebellar ataxia described was progressive and poorly responsive to immunomodulatory therapy; and (3) the potential for development of further autoimmune sequelae in response to immunosuppression, namely, the development of insulin-dependent diabetes in response to treatment with high-dose oral steroids.